Surgical and Orthodontic Management of Cleft Lip and Palate: A Comprehensive Review - Vigneswari MD, A.Srivel; Mishra, Nitesh; R, Akilan.; Purohit, Aastha; Santhi, K.; Gunasekaran, M. (Journal of Neonatal Surgery, 2025)
Cleft lip and palate (CLP) are among the most common congenital craniofacial anomalies, resulting from the incomplete fusion of embryonic facial prominences during development. The multifactorial causes of CLP involve genetic factors and environmental risks, such as maternal smoking and folic acid deficiency. In addition to the anatomical defect, CLP adversely affects feeding, speech, maxillary growth, and psychosocial well-being, necessitating a multidisciplinary treatment approach from infancy to adulthood. Management of CLP follows a structured protocol that aims to enhance both facial aesthetics and functional outcomes. Primary surgical interventions—including cleft lip repair within the first six months and cleft palate closure before 18 months—are crucial for early rehabilitation. Secondary treatments, such as alveolar bone grafting and orthognathic surgery, address residual skeletal and occlusal discrepancies. Recent advancements in surgical techniques and orthodontic management are pivotal for guiding maxillary development and ensuring long-term stability. Future innovations in tissue engineering, three-dimensional printing, and artificial intelligence-driven planning stand to improve surgical precision and patient outcomes. This review consolidates contemporary evidence to establish an effective, patient-centered framework for CLP management.